Design and pedagogical practices of an Inuit-focused Bachelor of Education program in Labrador - Sylvia Moore; Gerald Galway (University of Aberdeen, School of Education, 2018)
Memorial University's 2009 Presidential Task Force on Aboriginal Initiatives called for the establishment of a community-based teacher education program for Labrador. The Faculty of Education at Memorial and the Nunatsiavut Government (NG) subsequently worked together to develop an Inuit-focused primary-elementary pre-service program for Goose Bay, a community adjacent to Nunatsiavut. For NG, the training of local Inuit teachers in the Inuit Bachelor of Education (IBED) is an important step towards taking control of the K-12 education system in their land claim area. In this paper we explore the design and pedagogical practices of that program. The macro-level program design pays attention to context-relevant factors such as academic and cultural supports, program sequence and schedule, workload-family balance, and the selection of instructors. The curriculum design is guided by "Two-Eyed Seeing," a model that respects the differences in Western and Indigenous ways of understanding the world and draws on the strengths of both (Marshall, Marshall & Iwama, 2010). Inuit culture is infused, in all aspects of the IBED, through landbased experiences, Inutittut language training, the inclusion of Inuit Elders, and the use of Inuit specific resources. The pre-service teachers are developing pedagogical practices that: reflect Inuit ways of teaching and learning, embrace culturally relevant Inuit education within the context of provincial curricula, and align with the goals of The National Inuit Education Strategy (2011).